2001
DOI: 10.1002/1521-3765(20010917)7:18<3911::aid-chem3911>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Strategies for the Attachment of Fluorescing Reporter Groups to Peptide Nucleic Acids in Solution and on Solid Phase

Abstract: The site-selective conjugation of peptide nucleic acids (PNA) with fluorescent reporter groups is essential for the construction of hybridisation probes that can report the presence of a particular DNA sequence. This paper describes convergent methods for the solution- and solid-phase synthesis of multiply labelled PNA oligomers. The solid-phase synthesis of protected PNA enabled the selective attachment of fluorescent labels at the C-terminal end (3' in DNA) which demonstrated that further manipulations on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 84 publications
1
21
0
Order By: Relevance
“…Thus, we changed to the allyl ester (4, Scheme 1), which affords orthogonal removal condition to Fmoc-deprotection and also increases the solubility of the backbone submonomer in organic solvents. While this compound has been previously synthesized by transesterification from tert-butyl ester, 17 we have employed a convenient 2-step method starting from 2-Naminoethylglycine 18 (3) followed by carbamylation with Fmoc-N-hydroxysuccimide (Fmoc-NHS). We have found compound 3 to be a very useful precursor that may be produced and esterified easily on large scale (ca.…”
supporting
confidence: 88%
“…Thus, we changed to the allyl ester (4, Scheme 1), which affords orthogonal removal condition to Fmoc-deprotection and also increases the solubility of the backbone submonomer in organic solvents. While this compound has been previously synthesized by transesterification from tert-butyl ester, 17 we have employed a convenient 2-step method starting from 2-Naminoethylglycine 18 (3) followed by carbamylation with Fmoc-N-hydroxysuccimide (Fmoc-NHS). We have found compound 3 to be a very useful precursor that may be produced and esterified easily on large scale (ca.…”
supporting
confidence: 88%
“…10 While conjugation of fluorescent dyes to PNAs that have been removed from solid support and deprotected is a viable alternative, in practice such approach is more time-consuming and requires either changes in PNA structure (e.g., replacement of lysine with glutamic acid) or custom made monomers. 11,12 Labeling of the PNA N-terminus can be done either directly with an activated carboxylic acid derivative of the dye 10 or using custom made monomers, such as lysine conjugated with fluorescein at the ε-amino group. 13,14 Custom made monomers can be also used in labeling of the C-terminus; for example, loading the solid support with S - t -butylmercapto- l -cysteine allowed conjugation of the thiol group with maleimido functionalized rhodamine dye directly on solid support.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies indicated that the presumed helical distortion was not so dramatic as to completely prevent base pairing [23,24]. …”
Section: Post-synthetic Modification Of Nucleobasesmentioning
confidence: 99%